The Chinese in America : a history from Gold Mountain to the new millennium - edited by Susie Lan Cassel (Walnut Creek, CA : AltaMira Press, [2002] ©2002, 2002)
xii, 463 pages : illustrations, maps ; 23 cm
Papers from the Sixth Chinese American Conference, held July 9-11, 1999 and hosted by the Chinese Historical Society of Greater San Diego and Baja California.;Includes bibliographical references and index.